The Ethics of Facial Allotransplantation: A Systematic Review - Xiangxia Liu, MD, PhD; Sarah Langsdon, MD; Wesley Holloway; Shuqia Xu, MD; Qing Tang, MD; Yangbin Xu, MD, PhD; Sai Ram Velamuri, MD; William Hickerson, MD (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. Currently, there are more than 40 cases of facial allotransplantation performed by 13 different groups in 10 countries. Although it has become a potential option to reconstruct and restore the function and appearance of severely facially disfigured individuals, the ethical concerns of facial allotransplantation remain unsolved. We conducted a systematic review to better understand the ethical concerns on facial allotransplantation and the changing trends of the ethical debate over time.